The Complexity of the Implications of Globalization in the Context of the Current Global Economy - CREŢOIU, Raluca Ionela (Annals of Spiru Haret University. Economic Series, 2014)
Globalization represents a controversial phenomenon both because of its complexity and because of the various implications it has on the global economy. Globalization will act simultaneously on many levels, its effects being correlated with the diversity of the angles from which this phenomenon can be approached from – economic, social, politic, cultural, philosophic etc. The article represents an incursion into the issue regarding the implications and effects of globalization grouped in several areas of analysis such as the disappearance of borders, the effects on culture, the effects on the education, the impact on labour market impact and the phenomenon of immigration, the effects of globalization in the context of the food crisis underdevelopment and poverty. To complete the analysis that points out enough elements considered to be negative, at the end of the article, there are also approached the development opportunities that globalization can offer in terms of boosting the economic exchanges, the exchange of genuine cultural values and ensuring a transfer of information at a global scale, so necessary for the scientific and technological progress. The conclusions of the article weighs the many aspects highlighted, both negative and positive, and suggests a series of useful research directions in order to fathom the complex features of this concept so controversial – globalization.